The Villeneuve Necrology: MS. Grande Chartreuse 1 Cart. 22, volume 4: 1586–1640. Edited by John Clark. Pp. xiv + 286. Illustrated. (Analecta Cartusiana, 100:27.) Salzburg: Institut für Anglistik und Amerikanistik, 2004. isbn 3 900033 06 4. Paper €40 - Gribbin, Anselm J. (The journal of theological studies, 2006)
This fourth volume of transcripts from the ‘Villeneuve Necrology’, a late seventeenth-century manuscript conserved at La Grande Chartreuse, brings the list of obits of the Carthusian Order and its benefactors edited from there to the year 1640. These lists were culled from the cartae of the Carthusian general chapter and were written by a single scribe. The manuscript also contains annotations in the hand of Dom Palémon Bastin (d. 1933), a notable ‘copier’ of Carthusian source material. John Clark's transcripts are made all the more valuable because the original exemplares or ‘master-copies’ of the cartae, written by the ‘Scribe(s)’ of the Carthusian general chapter, are wanting for the years featured in this volume.